PENGEMBANGAN PERANGKAT PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN PENILAIAN PORTOFOLIO PADA PEMBELAJARAN MATEMATIKA BERORIENTASI KEMAMPUAN AWAL - Rufiana, Intan Sari; Mardiyana, Mardiyana; Iswahyudi, Gatut (Journal of Mathematics and Mathematics Education, 2014)
Abstract: The aims of this study were to: (1) produce a learning device in STAD cooperative learning model with a portfolio that was good for the subject of algebra in seventh grade junior high school, (2) know the effectiveness of cooperative learning of STAD type with portfolio assessment when it is viewed from early ability. This research was a kind of research and development. The development procedure used in this study was the development of a learning device according Thiagarajan et al, which was consisted of four stages: define, design, development, and disseminate. In disseminate stage, the experiment was conducted with portfolio assessment. Experiments conducted on the two junior high schools, they were Muhammadiyah Yanggong junior high school and Muhammadiyah Jenangan junior high school. Based on the inferential analysis, it showed that (1) the learning outcomes of students who were taught mathematics STAD cooperative learning with portfolio assessment was better than the mathematics learning outcomes of students who were taught STAD cooperative learning on the subject of algebra, (2) students who had high early ability had better performance than who had low early ability, (3) in the high ability, the students who were taught by using STAD cooperative learning model with portfolio assessment had better learning achievement than the students who were taught by using STAD cooperative model STAD without portfolio assessment, (4) in the low early ability, the students who were taught using STAD cooperative learning model with portfolio assessment had the same performance with STAD cooperative learning model without portfolio assessment, (5) the students who were taught by the STAD cooperative learning without portfolio assessment, students who had high early ability had better performance than who had low early ability, and (6) the students who were taught by using STAD cooperative learning model with portfolio assessment, the students who had high early ability had better performance than the students who had early ability.Key words: Cooperative STAD, Portfolio Assessment, Early ability